2009
DOI: 10.1007/s12663-009-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of shoulder function after functional neck dissection and selective neck dissection (Levels I, II, III) in patients with carcinoma of tongue: a comparative study

Abstract: Background and objectivesTo compare shoulder function with respect to pain and disability in patients who have undergone nerve sparing neck dissection i.e. selective neck dissection (levels I, II, III) and functional neck dissection as a part of their treatment modality for carcinoma tongue on a follow up of minimum six months. Material and methods A total of 100 patients were selected for this study. 50 patients who had undergone selective neck dissection (levels I, II, III) and 50 who underwent functional ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Patients with this disease often have advanced clinical neck metastasis at initial presentation, and deescalation of treatment without compromise of oncologic outcomes is the concept behind current HPV‐OPSCC–related research . In this report, complications of the neck dissection were low and prior authors have shown that both perioperative and long‐term complications, particularly related to shoulder morbidity, are significantly lower for SND than MRND.…”
Section: Discussionmentioning
confidence: 76%
“…Patients with this disease often have advanced clinical neck metastasis at initial presentation, and deescalation of treatment without compromise of oncologic outcomes is the concept behind current HPV‐OPSCC–related research . In this report, complications of the neck dissection were low and prior authors have shown that both perioperative and long‐term complications, particularly related to shoulder morbidity, are significantly lower for SND than MRND.…”
Section: Discussionmentioning
confidence: 76%
“…However, the extent of ND, as well as any adjuvant/nonsurgical treatment regimen, can influence health-related quality of life [ 11 14 ]. Shoulder dysfunction including scapula flaring, shoulder drop, and limited arm abduction attributed to spinal accessory nerve impairment, phrenic nerve injury, and chylous leakage, has been associated with the extent of ND [ 15 18 ]. Therefore, a less extensive surgical treatment regime while maintaining oncologic control would be preferable.…”
Section: Introductionmentioning
confidence: 99%